Teaching Vocabulary: Methods and Approaches - Khasanova K.B.; Safarova D.A (Global Scientific Publishing, 2022)
Vocabulary is one of the most important aspects of the foreign language teaching and learning. The word is a recognizable linguistic unit for children in their first language and so they will notice words in the new language. Often children are taught words in the new language by showing them objects that they can see and touch, and that have single word labels in the first language. This article discusses particularly problems and peculiarities of teaching and learning vocabulary.
Keywords: vocabulary; teaching; methods; strategies